Understanding the synergistic effect of CO2, H2S and fluid flow towards carbon steel corrosion. (February 2022) - Zhang, Shaohua; Li, Yanrui; Liu, Baosheng; Mou, Liming; Yu, Shuo; Zhang, Yuezhong; Yan, Xiaoyan
Abstract: The synergistic effect of CO2, H2 S and fluid flow towards carbon steel pipelines was studied by systematically evaluating the corrosion response of AISI 1020 carbon steel in aqueous solutions containing CO2 and CO2 /H2 S at various contents under the static and dynamic conditions at 60 °C. The results have revealed that the dissolved H2 S can impede the formation of FeCO3 crystals by the preferential adsorption process of FeHS a d s + to form the porous iron sulfide scale, through which the corrosive species, especially in dissolved CO2, can easily reach the steel/scale interface and accelerate the dissolution of steel matrix. On the other hand, the limited adsorption process of FeHS a d s +, enhanced mass transport of corrosive species/Fe 2+ along with easy spalling of iron sulfide scale with poor adhesion are expected under the action of fluid flow, ultimately aggravating the localized and general corrosion of carbon steel. Highlights: A synergistic mechanism of CO2, H2 S and fluid flow on the carbon steel corrosion exists. The initial corrosion products follow the solid-state reaction mechanism in CO2 /H2 S conditions. The occurrence of FeCO3 is primarily in the form of the amorphous structure at 10 ppm H2 S. The fluid flow contributes to the localized and accompanied general corrosion.